2015
DOI: 10.1017/ice.2015.295
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Barriers and Goals in Pediatric Oncology and Bone Marrow Transplantation: A Survey of Antimicrobial Stewardship Practitioners

Abstract: We undertook a cross-sectional survey of antimicrobial stewardship clinicians in North America and Australasia regarding practices, goals, and barriers to implementation of stewardship for pediatric oncology patients. Goals and barriers were similar regardless of clinician or institutional characteristics and geographic location. Strategies addressing these factors could help optimize antimicrobial use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…While we did not delve into this topic, the issue of prescriber opposition was explored in a recent study about stewardship barriers and goals in pediatric oncology and HCT. 31 Our survey also showed that monitoring is not done robustly in transplant patients with the exception of C.difficile rates, followed by antimicrobial costs. According to the 2016 IDSA/SHEA guideline, every ASP should track antimicrobial utilization in order to examine overall consumption or compare usage by unit, provider, or service in the hospital.…”
Section: Discussionmentioning
confidence: 83%
“…While we did not delve into this topic, the issue of prescriber opposition was explored in a recent study about stewardship barriers and goals in pediatric oncology and HCT. 31 Our survey also showed that monitoring is not done robustly in transplant patients with the exception of C.difficile rates, followed by antimicrobial costs. According to the 2016 IDSA/SHEA guideline, every ASP should track antimicrobial utilization in order to examine overall consumption or compare usage by unit, provider, or service in the hospital.…”
Section: Discussionmentioning
confidence: 83%
“…Yet, ASPs may result in reduced mortality [62, 63]. With continuously mounting evidence in support of improved patient outcomes due to ASPs, physicians can be further convinced of the benefit of a multidisciplinary approach to antimicrobial stewardship.…”
Section: Antibiotic Stewardshipmentioning
confidence: 99%
“…Physician or hospital practices may reflect local antibiograms, institutional stew-ardship initiatives, hospital formulary choices, or the reliance of transplant groups on historical practice outside the influence of a stewardship program. 26 Data regarding physician- or hospital-specific practice patterns were not available in this dataset so this hypothesis could not be evaluated. However, it should be considered in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…No specific recommendations exist for stewardship in transplant units. 26 Options for intervention recommended by the 2016 IDSA guidelines include prospective audit of antibiotic prescriptions with feedback to individual prescribers and formulary restriction. 27 Both strategies have been successfully implemented in an adult hematology/oncology and transplant units.…”
Section: Discussionmentioning
confidence: 99%